Southern African HIV Clinicians Society gender-affirming healthcare guideline for South Africa - Anastacia Tomson; Chris/tine McLachlan; Camilla Wattrus; Kevin Adams; Ronald Addinall; Rutendo Bothma; Lauren Jankelowitz; Elliott Kotze; Zamasomi Luvuno; Nkanyiso Madlala; Savuka Matyila; Anil Padavatan; et al. (AOSIS, 2021)
No abstract available.